Why do people keep their promises? An overview of strategic commitment (2015)
Strategic commitments, such as promises and threats, pose several problems to the standard model of economic rationality: first, they can only arise when there is an incentive to free ride; second, they need to be credible in order to manipulate the others' behaviour; third, once the commitment has succeeded, it is no longer in the agent's self interest to fulfil her commitment. Why, then, do people keep their promises (and threats)? This paper reviews the literature concerning the problem of commitment within the scope of pro-sociality and cooperation, and examines two mechanisms that enable credibility and trust: reputation and social emotions.